Intention to Consume Towards Functional Foods among Senior Citizens in Malaysia - Flaviana Ivy Febian; Sharifah Nurafizah Syed Annuar (Journal of International Business, Economics and Entrepreneurship)
The trend nowadays is that when consumers prefer convenient food compared to healthy food. Due to numerous health threats, the demands for health foods are increasing. This can be seen from the number of purchases of functional foods which have improved tremendously in the market. This study was conducted to examine the influence of perceived susceptibility, perceived benefits and cue to action on intention to consume functional food among senior citizen. The respondents were 250 conveniently selected senior citizen who are visiting shopping mall. Data were collected by using a selfadministered questionnaire. The findings revealed that one factor such as perceived benefit recorded a significant and positive influence on intention to consume functional food. On the other hand, perceived susceptibility and cue to action were deemed as not significant in influencing functional food consumption intention. Future study was also proposed.